Administrative Stressors in Pakistani Medical Schools: A Call for Identification and System-level Interventions - Shabiaa Nauman Aziz (Journal of the Pakistan Medical Association, 2024)
Dear Madam, Medical students consistently experience stress, depression, and burnout1 and Pakistani students are no exception to this2. Apart from academics, several other stressors have been reported, including lack of time to oneself, poor time management skills, work-life balance, and relationships with peers. A recent study3, conducted among students from nine medical schools in Florida, aimed to examine students’ perceptions regarding their most significant stressors. The results showed the spectrum of stress severity ranging from mild to severe and the impact of stressors was identified. This study also highlighted an under-researched stressor where students have noted administrative failures, including unpredictable schedules, lack of communication between faculty and students, confusing academic requirements, and misalignment of the curriculum with the competitive exams. It resonates with my peers and my experiences, suggesting that this problem is likely to exist in Pakistani medical colleges. A thorough search through PubMed and PakMediNet revealed that academic stressors are well documented. Although briefly mentioned in this study4, the administrative stressors have not been given much attention. These administrative stressors are easily preventable if identified. Therefore, there is a dire need for more research to specify these problems to develop measures in the context of Pakistani medical schools. This could be achieved by conducting student surveys and interviews, establishing focus groups and discussions, and analyzing the records of student complaints, academic performance, and administrative processes, thus providing a deep insight into potential issues. Furthermore, until these problems are researched, our medical educationists must regularly analyze whether our system is student-centric or impedes the smooth operations of students’ lives, and thus, device and implement system-level interventions that prioritize a more student-friendly environment. In conclusion, administration failures in medical school have an impact on the stress levels of the students3, but more research is required to specify these preventable stressors, which will help in alleviating some of the stress and thus improve the overall well-being of the medical students in Pakistan and ultimately the quality of healthcare provided.